Análise psicométrica dos itens de educação física do Exame Nacional do Ensino Médio (ENEM) via Teoria Clássica dos Testes - Sousa, Leandro Araujo de (2017)
In recent years the importance of large-scale evaluations in the Brazilian context has grown, with emphasis in this scenario on the National High School Examination (ENEM). With its reformulation in 2009, the skills and abilities of the Physical Education have been inserted in the reference matrix of this exam. In that same year, the method of analysis of the results, based on the Classical Tests Theory (CTT), was also changed, using the Item Response Theory (IRT), under justification of being more adequate to allow the comparability of the Results. With this, this research aimed to analyze the Physical Education items of ENEM from the years 2009 to 2014 from the CTT. For that, we used the microdata of the exam provided by the National Institute of Studies and Educational Research Anísio Teixeira (INEP). The following metric parameters were analyzed: validity, reliability, difficulty and discrimination. SPSS software version 20.0 was used as a resource. The items presented good correlation values and adequacy of the item sample. They presented scores of commonality and factorial loads inadequate for the composition of the test. The Exploratory Factor Analysis presented low explanation of the variance considering only one factor, even the scree plot indicating that the test is unidimensionality. The reliability values of the test were good, with no influence of physical education items. The difficulty and discrimination presented values acceptable in almost every year. However, in 2014 the test did not present unidimensionality, considering the explained variance, as well as in the graphic analysis. This year, the items presented high difficulty and low discrimination. Thus, it is concluded that the Language and Codes tests of the ENEM presented difficulties in proving the unidimensionality, although it presented good accuracy, with the exception of 2014 and some Physical Education items of the exam did not present adequate parameters. Such factors may compromise the validity of the measure and consequently the results of such examination.